The Welfare Effects of Vertical Integration in Multichannel Television Markets - Crawford, Gregory S.; Lee, Robin S.; Whinston, Michael D.; Yurukoglu, Ali (Econometrica, 2018)
We investigate the welfare effects of vertical integration of regional sports networks (RSNs) with programming distributors in U.S. multichannel television markets. Vertical integration can enhance efficiency by reducing double marginalization and increasing carriage of channels, but can also harm welfare due to foreclosure and incentives to raise rivals' costs. We estimate a structural model of viewership, subscription, distributor pricing, and affiliate fee bargaining using a rich data set on the U.S. cable and satellite television industry (2000?2010). We use these estimates to analyze the impact of simulated vertical mergers and divestitures of RSNs on competition and welfare, and examine the efficacy of regulatory policies introduced by the U.S. Federal Communications Commission to address competition concerns in this industry.